Small Satellites Missions and Applications - Battistini, Simone; Graziani, Filippo; Pontani, Mauro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the last 20 years, two factors have revolutionized the way space missions and applications are conceived, namely an increased access to space guaranteed by new launch providers and advances in miniaturized technologies. These two factors have rapidly made small satellites a reliable tool for scientific, commercial, and educational activities in space. Acting as a part of a larger mission along with larger satellites, or even substituting the latter in some cases, small satellites have now become a reality in modern space missions. This Special Issue aims to address the recent advances in small satellites' technology and the resulting impact on space missions.